Bi-Mn diatomic interaction on SOD zeolite substrate promotes electrochemical methanol oxidation. (September 2022) - Wei, Pengyan; E, Yifeng; Jiang, Yuying; Chen, Peng; Li, Li; Qian, Kun
Abstract: The strategy of diatomic synergy is applied to the in-situ synthesis of electrode catalyst material for methanol fuel cells. During the one-pot synthesis in hydrothermal conditions, the doped Bi and Mn atoms are highly dispersed on and immobilized into the SOD zeolite cage structure as nanocrystals with trace amounts to form the novel Bi/Mn/SOD composite catalyst. The as-synthesized Bi and Mn NPs were confined in a rigid SOD nano-cage to maintain the stability and catalytic activity of the monodisperse state. Several key problems to be solved in methanol fuel cell applications are its energy density, catalytic efficiency, stability, and cost. Through the combined action of Mn and Bi, the composite electrode performed high activity in the methanol oxidation reaction (MOR) with a high current density of 45.9 mA cm −2 without precious metal and with high stability in 10 M methanol without any catalyst poisoning.